Analysis of Employee Expenditure Budget Preparation at the Food Security Office of Deli Serdang Regency - Hutahaean, Sondang Lastiur; Nasution, Dito Aditia Darma; Junawan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The purpose of this study is to find out the stage of preparing the 2024 employee expenditure budget at the Deli Serdang Regency Food Security Office. The data used in this study are primary and secondary data. This study uses a quantitative descriptive method. The type of data collection used is by interviews and document analysis for data collection. The results of this study show that the preparation of employee spending budgets at the Deli Serdang Regency Food Security Office has been in accordance with the needs of employees effectively and has been in accordance with existing procedures. The preparation of the employee expenditure budget by the budget preparation team of the Deli Serdang Regency Food Security Office has carried out its duties well.